Control of Particle Adsorption for Stability of Pickering Emulsions in Microfluidics. Issue 37 (20th August 2018) - Yao, Xiaoxue; Liu, Zhou; Ma, Mingze; Chao, Youchuang; Gao, Yongxiang; Kong, Tiantian
Abstract: Studying the stability of Pickering emulsion is of great interest for applications including catalysis, oil recovery, and cosmetics. Conventional methods emphasize the overall behavior of bulk emulsions and neglect the influence of particle adsorbing dynamics, leading to discrepancies in predicting the shelf‐life of Pickering emulsion–based products. By employing a microfluidic method, the particle adsorption is controlled and the stability of the Pickering emulsions is consequently examined. This approach enables us to elucidate the relationship between the particle adsorption dynamics and the stability of Pickering emulsions on droplet‐level quantitatively. Using oil/water emulsions stabilized by polystyrene nanoparticles as an example, the diffusion‐limited particle adsorption is demonstrated and investigated the stability criteria with respect to particle size, particle concentration, surface chemistry, and ionic strength. This approach offers important insights for application involving Pickering emulsions and provides guidelines to formulate and quantify the Pickering emulsion–based products. Abstract : A droplet microfluidic method to probe the dynamic adsorption of colloidal particles onto oil–water interfaces is presented. This method is used to examine the stability of generated Pickering emulsion droplets and quantify the critical surface particle coverage to prevent droplet coalescence. The generalizable approach has important implications for designing and formulating particle‐stabilized emulsion‐based products.